Penyesuaian Dosis Digoxin pada Pasien Gagal Jantung di RSUD Margono Soekardjo Purwokerto - Masita Wulandari Suryoputri; Laksmi Maharani; Ika Mustikaningtias (Fakultas Farmasi Universitas Pancasila, 2021)
Due to the high prevalence of heart failure in Indonesia causes the use of digoxin is increasing. The drug level in blood needs to be monitored because digoxin is a narrow therapeutic index drug. It is necessary to adjust the dose in the patient, so that clinical outcomes are achieve and toxic effects can be avoided if the estimated drug levels in the blood do not match the therapeutic range. The maintenance dose of oral digoxin is 0.0625 - 0.125 mg / day for heart failure patients and it is expected that the therapeutic range of digoxin in the blood range from 0.5 to 0.9 ng / ml. The purpose of this study was to determine the estimation of digoxin levels in blood in patients with heart failure and the calculation of dosage adjustments using a pharmacokinetic approach so that blood levels of drugs ware in the therapeutic range. This research employs a quantitative observational method conducted prospectively by using a total sampling technique. The results showed that the digoxin level of 4 patients (13,33%) were in the range of therapeutic range (0,50 – 0,90 ng/ml) and 26 patients (86,67%) exceed the therapeutic range (>1,00 ng/ml). Digoxin dose adjustment was made in 26 patients (86,67%) individually with an interval of every 24 hours in order to achieve Css according to the therapeutic range. Based on the results it can be concluded that in heart failure patients who have blood digoxin levels exceed the therapeutic range need dose adjustments to improve clinical outcomes and prevent toxicity in patients.